Trade, Wages and Collective Bargaining: Evidence from France. (May 2015) - Carluccio, Juan; Fougère, Denis; Gautier, Erwan
<x xml:space="preserve">Abstract</x> We estimate the impact of international trade on wages using data for French manufacturing firms. We instrument firm‐level trade flows with firm‐specific instrumental variables based on world demand and supply shocks. Both export and offshoring shocks have a positive effect on wages. Exports increase wages for all occupational categories while offshoring has heterogeneous effects. The impact of trade on wages varies across bargaining regimes. In firms with collective bargaining, the elasticity of wages with respect to exports and offshoring is higher than in firms with no collective bargaining. Wage gains associated with collective bargaining are similar across worker categories.